2017
DOI: 10.1021/acs.jpca.6b10980
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Hydroxide Ion Release From a Series of Acridinol Photobases

Abstract: The excited-state heterolysis of acridinol-based derivatives leads to the release of the OH ion and the formation of the corresponding acridinium cations. To evaluate the parameters that control the reaction barriers, the kinetics of excited-state OH release from a series of acridinol photobases were studied using transient absorption spectroscopy. The rate constants were obtained in three solvents (methanol, butanol, and isobutanol), and the data were modeled using Marcus theory. The intrinsic reorganization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Photoacids and photobases, molecular systems that respectively exhibit a profound increase in acidity or basicity, , are ideal molecular tools to study proton transport dynamics on ultrafast time scales using short pulse laser systems. , Proton dissociation to or proton abstraction from water and alcohol solvents and photoacid–base neutralization reactions have been investigated with picosecond time-correlated single photon counting, femtosecond UV–vis and UV–IR pump–probe techniques. A special class are so-called bifunctional photoacids and photobases, where proton-donating and -accepting sites are part of the same molecular system, with a well-defined number of solvent molecules constituting the proton transport pathway between donating and accepting sites.…”
Section: Introductionmentioning
confidence: 99%
“…Photoacids and photobases, molecular systems that respectively exhibit a profound increase in acidity or basicity, , are ideal molecular tools to study proton transport dynamics on ultrafast time scales using short pulse laser systems. , Proton dissociation to or proton abstraction from water and alcohol solvents and photoacid–base neutralization reactions have been investigated with picosecond time-correlated single photon counting, femtosecond UV–vis and UV–IR pump–probe techniques. A special class are so-called bifunctional photoacids and photobases, where proton-donating and -accepting sites are part of the same molecular system, with a well-defined number of solvent molecules constituting the proton transport pathway between donating and accepting sites.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the substituent (‐CN<‐CF 3 <‐H<‐OH<‐NMe 2 ) at the para position of the phenyl ring of PhAcOH and the influence of the solvent polarity (H 2 O<CH 3 OH<n‐BuOH<i‐BuOH) on the photoreactivity of the acridane core was also demonstrated [13] . This observation can be rationalized by the stabilization of the positive charge of the acridinium species by electron donating functional groups and by polar solvents.…”
Section: Physico‐chemical Propertiesmentioning
confidence: 85%
“…BuOH) on the photoreactivity of the acridane core was also demonstrated. [13] This observation can be rationalized by the stabilization of the positive charge of the acridinium species by electron donating functional groups and by polar solvents. This behavior was evidenced by the rate constant decay of the acridane S 1 state increasing upon increasing the electron donating nature of the functional group.…”
Section: Chemiochromic and Photochromic Propertiesmentioning
confidence: 99%
“…28 Their one-electron oxidized counterparts, the cations 10-methyl-9phenylacridinium [XNCH 3 ] + , 9-phenylxanthenium [X O] + , and 9-phenylthioxanthenium [XS] + , shown in Scheme 1, are interesting in their own rights as intermediates in turn-on fluorescent photo-and electrochromic switches, 29−31 excitedstate photohydrides 32 and photobases. 33,34 Our interest in these radicals stemmed from the desire to incorporate them into radical-based organic materials, which has never been reported to date. Given the rich and interdisciplinary chemistry centered on these three systems, the electrochemical interconversion between radicals and cations should already be well established; however, a literature survey revealed that this is not exclusively true; conflicting evidence has been published on the reversibility of these radical/cation redox couples.…”
mentioning
confidence: 99%
“…In the nearly 100 years since that time, these radicals have been implicated as intermediates in numerous systems for the study of potential NADH/NAD + analogues, , catalytic photo-oxidants, and hydrogen evolution catalysts . Their one-electron oxidized counterparts, the cations 10-methyl-9-phenylacridinium [ XNCH 3 ] + , 9-phenylxanthenium [ XO ] + , and 9-phenylthioxanthenium [ XS ] + , shown in Scheme , are interesting in their own rights as intermediates in turn-on fluorescent photo- and electrochromic switches, excited-state photohydrides and photobases. , …”
mentioning
confidence: 99%